FRAUD TRIANGLE: BROKEN WINDOWS THEORY IN PREVENTION OF OPPORTUNITIES (Third Sector Social Economic Review, 2018)
The leading companies in the world have been forced to end their commercial activities by incurring high costs due to fraudulent transactions. These actions have created negative effects on the world economy by causing the low and middle class to become unemployed and the environment of confidence in the capital markets. For this reason, one of the effective ways of eliminating financial losses in enterprises is the prevention of fraud and irregularities. In the literature, elements that cause fraudulent acts have been discussed for a long time. The discussions focused on the concept of the Fraud Triangle, which explains the factors that cause fraudulent transactions. In this study, on the bases of the efforts to understand and prevent fraudulent transactions, it is tried to relate to opportunity factor of Fraud Triangle with the Broken Windows Theory, which suggests that the symptoms of irregular and distorted behavior trigger larger crimes and lead to the spread of crime, in the context of weakness of internal control.
Keywords: Fraud; Fraud Triangle; Internal Control; Internal Audit; Broken Windows Theory